Metagenomic water quality monitoring with a portable laboratory - Acharya, K.; Blackburn, A.; Mohammed, Jemila; Haile, Alemseged Tamiru; Hiruy, A.M.; Werner, D. (Elsevier, 2020)
We describe the technical feasibility of metagenomic water quality analysis using only portable equipment, for example mini-vacuum pumps and filtration units, mini-centrifuges, mini-PCR machines and the memory-stick sized MinION of Oxford Nanopore Technologies, for the library preparation and sequencing of 16S rRNA gene amplicons. Using this portable toolbox on site, we successfully characterized the microbiome of water samples collected from Birtley Sewage Treatment Plant, UK, and its environs. We also demonstrated the applicability of the portable metagenomics toolbox in a low-income country by surveying water samples from the Akaki River around Addis Ababa, Ethiopia. The 16S rRNA gene sequencing workflow, including DNA extraction, PCR amplification, sequencing library preparation, and sequencing was accomplished within one working day. The metagenomic data became available within 24e72 h, depending on internet speed. Metagenomic analysis clearly distinguished the microbiome of pristine samples from sewage influenced water samples. Metagenomic analysis identified the potential role of two bacterial genera not conventionally monitored, Arcobacter and Aeromonas, as predominant faecal pollution indicators/waterborne hazards. Subsequent quantitative PCR analysis validated the high Arcobacter butzleri abundances observed in the urban influenced Akaki River water samples by portable next generation sequencing with the MinION device. Overall, our field deployable metagenomics toolbox advances the capability of scientists to comprehensively monitor microbiomes anywhere in the world, including in the water, food and drinks industries, the health services, agriculture and beyond.